2017
DOI: 10.1002/anie.201700389
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Radical–Radical Distances in Light‐Active Proteins and Their Implication for Biological Magnetoreception

Abstract: Light-generated short-lived radial pairs have been suggested to play pivotal roles in cryptochromes and photolyases.Cryptochromes are very probably involved in magnetic compass sensing in migratory birds and the magnetic-fielddependent behavior of insects.W ee xamined photo-generated transient states in the cryptochrome of Drosophila melanogaster and in the structurally related DNA-repair enzyme Escherichia coli DNAp hotolyase.U sing pulsed EPR spectroscopy, the exchange and dipolar contributions to the electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 51 publications
0
40
1
Order By: Relevance
“…6 for model of the effect of the MF on the cryptochrome photocycle). It should be added that attempts in the literature to link biological magnetosensing to forward electron transfer events in cryptochrome (see, e.g., Solov'yov et al 2007;Maeda et al 2012;Mouritsen and Hore 2012;Dodson et al 2013;Biskup 2013;Evans et al 2015;Hong and Pachter 2015;Lüdemann et al 2015;Müller et al 2015;Bialas et al 2016;Kattnig et al 2016;Nohr et al 2016Nohr et al , 2017Worster et al 2016;Van der Straeten et al 2018) are not supported by the biological data neither in birds (Wiltschko et al 2016) nor (as shown in this study) in plants.…”
Section: Discussioncontrasting
confidence: 57%
“…6 for model of the effect of the MF on the cryptochrome photocycle). It should be added that attempts in the literature to link biological magnetosensing to forward electron transfer events in cryptochrome (see, e.g., Solov'yov et al 2007;Maeda et al 2012;Mouritsen and Hore 2012;Dodson et al 2013;Biskup 2013;Evans et al 2015;Hong and Pachter 2015;Lüdemann et al 2015;Müller et al 2015;Bialas et al 2016;Kattnig et al 2016;Nohr et al 2016Nohr et al , 2017Worster et al 2016;Van der Straeten et al 2018) are not supported by the biological data neither in birds (Wiltschko et al 2016) nor (as shown in this study) in plants.…”
Section: Discussioncontrasting
confidence: 57%
“…S2C and Table 1). This yielded electron-electron interaction parameters of −8.2 and +0.03 MHz for D and J ex , respectively, from which a distance of 2.12 nm can be calculated (22). This distance closely mirrors that for FAD-TrpD (2.09 nm) by crystallography (20) and permits exclusion of the involvement of a [FAD•••TrpC] radical pair (1.75 nm) ( Table 1) in wild-type clCRY4.…”
Section: Radical Pair Formation In Pigeon Clcry4mentioning
confidence: 99%
“…The effect has been attributed to the Radical Pair Mechanism (RPM), which relates reaction outcomes to hyperfine-driven spin dynamics of a photo-generated radical pair within cryptochrome [4][5][6]. The hyperfine mechanism applies here despite the immobilisation of the radicals in the protein matrix, because an efficient charge-separation pathway exists that yields a well-separated radical pair in which inter-radical interactions are weak [18] compared to the dominating hyperfine interactions. In the mentioned in vitro experiments, this pair consists of a flavin adenine dinucleotide co-factor (FAD, here abbreviated as F) anion and a cation derived from the third tryptophan (W) of a highly-conserved electron transfer chain (the so-called tryptophan triad/tetrad [19]; see Figure 1A), i.e.…”
Section: Introductionmentioning
confidence: 99%